Thermodynamic optimization of the recuperative heat exchanger for Joule–Thomson cryocoolers using response surface methodology. (December 2015) - Liu, Yingwen; Liu, Liu; Liang, Lili; Liu, Xin; Li, Jiapeng
Highlights: Response Surface Methodology was developed to analyze the heat exchanger. The available work loss minimization was introduced as a new criterion. The interacting effects of geometric parameters were considered in the study. The optimum geometric parameters of the heat exchanger were acquired and verified. Abstract: In this paper, a numerical study is performed to investigate the effects of geometrical parameters on the thermodynamic performance of the helically coiled recuperative heat exchanger in a Joule–Thomson (J–T) cryocooler. A novel optimization model is developed based on the available work loss minimization for the recuperative heat exchanger. The experiments are conducted based on four factors: L, Dt, S, Ds, one level: Nd, and the results are analyzed according to the principle of Response Surface Methodology (RSM). The final predicted optimum combination of geometrical parameters for the heat exchanger is: L  = 430.5 mm, Dt   =   0.45 mm, S  = 5.41, Ds   =   4.3 mm. The optimization results are in good agreement with our model, and the deviations of predicted values are less than 1.32%. The model and results presented here for the optimization of the heat exchanger can provide helpful guidance and a new way for the optimization of J–T cryocooler.